The Psychological Impact of Family Disharmony - Swastini, Swastini; Rouful Hakim, Muhamad; Iskandar, Iskandar; Jannah, Siti Roudhotul (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
Everyone who is married certainly wants to have a harmonious family and have children who can grow up feeling happy. However, not all married couples succeed in building a harmonious household, because uniting two thoughts and two different desires is not something that easy to do. Sometimes emotions and prioritizing each other's egos cause arguments in a family. However, parental quarrels and household disharmony will have a negative influence on the child's psychological condition. Children who often witness their parents fighting will grow up to be gloomy individuals, easily stressed, tend to close themselves off from other people, experience inner burdens and be less happy. Whether you realize it or not, a child's strong sense of self-confidence arises when both parents live side by side in harmony. If a child is in a family environment that is not harmonious, he will lose his motivation and enthusiasm so that the child will become less confident and feel like he has lost the role model he should have received from his parents. The impact of family disharmony on children's psychology is that conditions of disharmony in the family environment can have serious consequences for children's mental and emotional well-being. Therefore, it is important for parents to understand that disharmony in the family has a significant impact on children's psychological well-being, so efforts are needed to create a harmonious family environment and provide and provide a healthy foundation for children's psychological development Keywords: Disharmony Family, Psychological Impact on Family